The long-term labor market effects of parental unemployment - Bernhard Schmidpeter (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
I investigate the impact of parental unemployment on children's educational attainment and long-run labor market outcomes in Austria. I find that parental unemployment shortly before an important educational decision by parents for their children lowers a child's probability of holding a university degree by more than 5 percentage points. I do not find that income is affected at the beginning of a child's labor market career along the distribution, but I find a gradual deterioration later on. A substantial share of these long-term losses can be explained by the lower parental investment decision. My results emphasize the intergenerational and longlasting consequences of parental unemployment. – – Ich untersuche die Auswirkungen elterlicher Arbeitslosigkeit auf das Bildungsniveau und den langfristigen Arbeitsmarkerfolg von Kindern. Es zeigt sich, dass elterliche Arbeitslosigkeit kurz vor einer wichtigen Bildungsentscheidung der Eltern für ihre Kinder die Wahrscheinlichkeit, dass ein Kind einen Hochschulabschluss erlangt, um mehr als 5 Prozentpunkte verringert. Elterliche Arbeitslosigkeit hat keine Auswirkungen auf das Einkommen der Kinder zu Beginn ihrer Arbeitsmarktkarriere, aber ich finde zunehmende und langfristige Einkommensverluste. Ein wesentlicher Teil dieser langfristigen Verluste lassen sich durch eine geringere Investitionsentscheidung der Eltern erklären. Meine Ergebnisse unterstreichen die generationsübergreifenden und langfristigen Folgen von Arbeitslosigkeit.
Keywords: C21; I23; J13; J31; J64; 330; parental unemployment; intergenerational effects; long-term effects; unemployment; wage loss; decomposition